THE STRATEGIC ROLE OF THE SCHOOL PRINCIPAL IN THE IMPLEMENTATION OF THE MOVING SCHOOL PROGRAM: A CASE STUDY AT SMAN 1 KELAM PERMAI - Suharto, Suharto (Universitas Tanjungpura, 2026)
The School Driver Program initiated by the Ministry of Education, Culture, Research, and Technology aims to enhance the quality of education through school transformation. This study employs a qualitative approach with a case study design to understand the principal's strategies in implementing the School Driver Program at SMA Negeri 1 Kelam Permai. Primary data were obtained through in-depth interviews and direct observations, while secondary data were collected from relevant documents. The findings indicate that the principal plays a central role in the planning and implementation processes of the program. The success of this program is influenced by several factors, including systematic planning and close collaboration with all stakeholders. The measurable positive impacts on academic achievement and student participation suggest that this program is worthy of continuation and further development.